Relapse in obesity management: does increased appetite and reduced energy expenditure play a role? - Martins, Cátia (Henry Stewart Talks, 2022)
Drivers of weight regain, Compensatory theory of weight regain, Energy expenditure in weight regain, Metabolic adaptation after weight loss, Changes in appetite following weight loss, Normalisation theory of weight regain